Систематика рода ящурка — Eremias (Sauria, Reptilia) — в связи с очагами развития пустынно-степной фауны Палеоарктики - Щербак, Н.Н. (Вестник зоологии, 1971)
On the basis of studying the history of the problem taxonomic and zoogeographical data, it is proved that the genus Eremias (23 species) is an autochthon of Asia and its distribution is restricted by this continent. The genus Eremias, in the interpretation of Boulanger who referred the African species to it as well, is a combined group. The division of the group into genera is suggested: Mesalina (12 species, including M. guttulata coming to the USSR territory), Lampreremias (4 species), Pseueremias (8 species), Taenieremias (2 species), Meroles (6 species). On the basis of studying faunistic complexes of the Eremias species, their distribution by areals anil biotopes, the focuses of deserl-sleppe iauna of Paleoarctic are distingushed.